2010
DOI: 10.1345/aph.1m550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Metformin and Topiramate in Prevention and Treatment of Second-Generation Antipsychotic–Induced Weight Gain

Abstract: Data for the use of metformin and topiramate in the treatment and prevention of second-generation antipsychotic-induced weight gain are limited. Both may be effective in helping patients lose weight via mechanisms that have yet to be clearly defined. The use of metformin results in greater weight loss than topiramate, and topiramate is associated with more risks and may compromise the treatment of schizophrenia. Treatment of antipsychotic-induced weight gain with metformin may be an option after lifestyle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 73 publications
2
34
1
1
Order By: Relevance
“…Furthermore, a decrease in glucose, cholesterol, triglyceride levels and systolic and diastolic blood pressure is also reported [ 43 ] . A recent review has gathered the limited data about these 2 and concluded that metformin results in greater weight loss than topiramate, while topiramate is associated with more risks [ 44 ] . This review recommended that lifestyle and dietary changes should be considered fi rst.…”
Section: Mean (Sd)mentioning
confidence: 99%
“…Furthermore, a decrease in glucose, cholesterol, triglyceride levels and systolic and diastolic blood pressure is also reported [ 43 ] . A recent review has gathered the limited data about these 2 and concluded that metformin results in greater weight loss than topiramate, while topiramate is associated with more risks [ 44 ] . This review recommended that lifestyle and dietary changes should be considered fi rst.…”
Section: Mean (Sd)mentioning
confidence: 99%
“…The effect size for medication differences is small. Metformin may limit antipsychotic induced weight gain (Bushe et al, 2009;Ellinger et al, 2010), and Scottish Intercollegiate Guideline Network (SIGN) guidelines recommend consideration of metformin in those experiencing such drug induced weight gain (regardless of diabetes diagnosis) (Scottish Intercollegiate Guidelines Network (SIGN), 2013). These 2013 guidelines may influence future prescribing habits but should not have impacted on this 2010 data extract.…”
Section: Impact Of Antipsychotic Medication On Glycaemic Controlmentioning
confidence: 99%
“…Findings from these systematic reviews are briefly summarised in Table 2 2,3,[14][15][16]18 and in Table 3. 9,10,17,19,20 Most of the systematic reviews on metformin were based on eight randomised controlled trials (RCTs). Six trials involved adults (see Table 4) [21][22][23][24][25][26] and two trials related to paediatrics (details can be found elsewhere).…”
Section: Pharmacological Optionsmentioning
confidence: 99%
“…Not every trial controlled for interventions that can affect weight (including additional medications, lifestyle and dietary interventions). 9 Weight loss was demonstrated in most studies in addition to lifestyle intervention. 3 This makes determining the contribution of metformin, on its own, in reducing weight difficult; however, Wu et al 25 demonstrated that metformin alone reduces more weight (-2.7kg) than lifestyle interventions only (-1.4kg), and that the combination of lifestyle intervention + metformin was more effective (-5kg) than either intervention alone.…”
Section: Limitation Of the Current Evidence Basementioning
confidence: 99%
See 1 more Smart Citation